Energy conservation routing algorithm for wireless sensor networks using hybrid optimisation approach. (2018) - Logambigai, R.; Kannan, A.
In designing wireless sensor network (WSN), the conversation of energy is an important issue to prolong the network lifetime. Most of the energy is wasted during transmission. To overcome this, an energy efficient routing protocol is proposed in this paper using a hybrid optimisation technique. Moreover, a nature inspired hybrid optimisation approach called bacterial swarm optimisation (BSO) is used in this work for energy optimisation in WSN. BSO is an amalgam of two optimisation techniques namely particle swarm optimisation (PSO) and bacterial foraging optimisation (BFO). BSO is used to identify the optimal next hop node for each gateway which in turn results in optimal route. The optimal relay nodes are selected based on lifetime of the gateways and distance in hops between gateways and base station. The results obtained from the simulation show that this proposed BSO based algorithm outperforms the other existing algorithm for routing.